GIS Analysis of Spatial Associations Between Epicenters of Earthquakes, Geological Features and Oil Fields in Kuwait - Al-Azmi, Hamad Jouhem (Journal of engineering sciences and information technology, 2017)
One of the fundamental aspects in understanding spatial distributions of earthquakes is their relation to the associated geological features at different scales of observation. This is best studied systematically by the techniques available in GIS (Geographic Information System). In this Project, various GIS techniques are applied on in identifying the spatial relationships between the epicenters of earthquakes and the associated geological features in Kuwait. The involved in the digitization of the lithological and structural features, and overlay analyses between these features and the locations of epicenters and oil fields in Kuwait. The results clearly spatial associations epicenters and oil fields, and also epicenters and certain geological and structural features. The obtained results could help in further statistical modeling